2019
DOI: 10.18585/inabj.v11i3.618
|View full text |Cite
|
Sign up to set email alerts
|

Serum Free Zinc as A Predictor for Excessive Function of Pancreatic Beta-Cells in Central-Obese Men

Abstract: BACKGROUND: Central obesity is known as a risk factor for type 2 diabetes mellitus (T2DM). Its development is influenced by many factors such as a progressive failure of pancreatic beta cell function. The beta cells increase their function to secret insulin along T2DM development to compensate before it becomes exhausted. Zinc (Zn) plays a crucial role in beta cell function and insulin secretion. The majority of Zn in serum are bound to protein which is not readily available interact with cells. The free Zn in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The present study observed the different mean scores of HOMA-β between the IR and non-IR groups and between two classes of BMI classes among benign neoplasm cases; meanwhile, there was no statistical difference among malignant cases. It was probably due to the lower prevalence of obese and overweight participants in the malignant group, thus making the marker measurement results less reliable ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study observed the different mean scores of HOMA-β between the IR and non-IR groups and between two classes of BMI classes among benign neoplasm cases; meanwhile, there was no statistical difference among malignant cases. It was probably due to the lower prevalence of obese and overweight participants in the malignant group, thus making the marker measurement results less reliable ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…HOMA-β classification depicts the function of the pancreatic β-cells ( 64 ). The classification used for the HOMA-β tests was determined by an Asian study from Japan using a cut-off point by tertile: ≤76.25 (low value; suggesting β-cell dysfunction); 76.25-122.13 (medium value; indicating normal β-cell function); and ≥122.13 (high; suggesting the excessive function of insulin secretion in β-cells, commonly found in central obesity) ( 53 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous study showed that there was a good correlation between serum free Zn with HOMA-B, the concentration of serum free Zn increased along with HOMA-B and indicating the excessive function of beta cells and interestingly, it reduced dramatically in T2DM along the decrease beta cell function. (55) Based on that finding, Zn showed a potential feature to predict beta cell failure at the early stage of chronically beta cells stress when compensate the high demand of insulin in central obesity. The complete Zn features in beta cell protection from oxidative stress and inflammation and insulin production illustrated in Figure 5.…”
Section: The Role Of Scfas In Pancreatic Beta Cell Healthymentioning
confidence: 94%